2006
DOI: 10.1007/s10735-006-9021-1
|View full text |Cite
|
Sign up to set email alerts
|

Actin cytoskeleton remodelling in the anterior pituitary folliculostellate cell line TtT/GF: participation of the actin-binding protein cortactin

Abstract: We have previously shown that the folliculostellate (FS) cells of the anterior pituitary change their shape from stellate (type I) to polygonal (type II) coincidently with variations in the secretory activity of the pituitary. To elucidate the mechanisms involved in this switch in phenotypes, here we studied the impact of serum factors on the morphology of the FS cell line TtT/GF. TtT/GF cells cultured in serum-containing medium displayed elongated shapes and membrane ruffles similarly to type I cells. Serum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…We have shown that cell-to-cell communication transiently increased following PKC-mediated Cx43 phosphorylation in Ser 368 (Meilleur et al, 2007); however, the persistent increase in P-Cx43 levels is accompanied by a reduced Cx43-mediated intercellular communication (Bao et al, 2004;Lampe et al, 2000;Meilleur et al, 2007). Cortactin phosphorylation in tyrosine 421 has been associated with increased actin polymerization (Tehrani et al, 2007) and cell adhesion stabilization (Well et al, 2004;Zheng et al, 2005). Thus, the Cx43 dephosphorylation and cortactin phosphorylation documented here early in development may reflect increasing intercellular junction-actin cytoskeleton interactions within the seminiferous epithelium during this period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that cell-to-cell communication transiently increased following PKC-mediated Cx43 phosphorylation in Ser 368 (Meilleur et al, 2007); however, the persistent increase in P-Cx43 levels is accompanied by a reduced Cx43-mediated intercellular communication (Bao et al, 2004;Lampe et al, 2000;Meilleur et al, 2007). Cortactin phosphorylation in tyrosine 421 has been associated with increased actin polymerization (Tehrani et al, 2007) and cell adhesion stabilization (Well et al, 2004;Zheng et al, 2005). Thus, the Cx43 dephosphorylation and cortactin phosphorylation documented here early in development may reflect increasing intercellular junction-actin cytoskeleton interactions within the seminiferous epithelium during this period.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Changes in form and phosphorylation status of the cortactin are stage-dependent. Cortactin is associated with cell migration (Huang et al, 2003;van Rossum et al, 2006;Zheng et al, 2005). Here, near the apex, the mature spermatids migrate from the seminiferous epithelium to the lumen of the tubule following completion of their differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…1A, control, 24 to 96 hours). We have previously shown that the actin cytoskeleton of serum-cultured TtT/GF cells is characterised by its association with the subplasmalemmal region and by the presence of thin cytoplasmic actin cables (Zheng et al, 2005). Treatment of TtT/GF cells with TNFα for increasing periods of time (0-96 hours) induced the cells to acquire a rounded shape and to detach from the culture support (Fig.…”
Section: Long-term Tnfα Treatment Induces Apoptosis Of Ttt/gf Cellsmentioning
confidence: 87%
“…The cytoskeleton fractions were dissolved in RIPA buffer (150 mM NaCl, 1% NP-40, 0.5% DOC, 0.1% SDS, 50 mM Tris pH 8). The characterisation of subcellular fractions had been be done and described before (Zheng et al, 2005).…”
Section: Preparation Of Subcellular Fractionsmentioning
confidence: 99%
“…Cortactin is located at sites of actin assembly in lamellipodia [101], and is likely involved in endosomal movement in fibroblasts [102]. It is also implicated in controlling shape-changes of folliculostellate cells of the anterior pituitary [103], and in aberrant cell motility, such as cancer cell migration and invasion [104,105].…”
Section: Cortactin Promotes Branching and Stabilization Of Actin Filamentioning
confidence: 99%